The Effect of Endotracheal Suction on Hemodynamics of Neurological Patients: A Literature Review - Aris, Rahaemil Jannah; Arafat, Rosyidah; Rachmawaty, Rini (Alta Dharma Publisher, 2025)
Introduction: One of the challenges in caring for neurology patients is the risk of increased intracranial pressure. Endotracheal suction is a routine nursing action but this procedure is reported can affect hemodynamic parameters. Artificial Airway Suction endotracheal recommends open and closed endotracheal suction safety and effective but several studies recommend the use of closed endotracheal suction so that study of the effect of endotracheal suction is needed. Objective: To determine the effect of endotracheal suction on hemodynamics of neurology patients. Method: The author was using a flow chart prism from 3 databases, namely Pubmed, Research Gate and Europe PMC with quantitative articles and Randomized Controlled Trial studies. Results: There were 11 articles found by the author, 8 articles compared the effect of endotracheal suction on hemodynamics, showing a significant effect between the use of open endotracheal suction and closed endotracheal suction on several hemodynamic assessment variables, which results were found more stable hemodynamic in the use of closed endotracheal suction, 3 articles looked at the effect of open endotracheal suction on oxygen saturation and all concluded that there was an effect of open endotracheal suction. 4 articles recommended the use of closed endotracheal suction in critical care areas because there were fewer physiological disorders. Conclusion: The use of closed endotracheal suction is recommended for neuro patients because of the more stable hemodynamic effects. The author suggests further studies on the effect of endotracheal suction of neurology patients spesifik for increased intracranial pressure.